Utilization of water hyacinth as a reducing agent in microwave-assisted synthesis of zinc oxide nanoparticles for photocatalytic applications - Nugraha Ramadhan; Nathania Safitri Indar Permana; Achmad Bagas Fadillah; Andre Susanto; Muhammad Aulia Rahman Sulaiman (Environmental and Materials, 2026)
Background: The textile industry is the second largest contributor to industrial pollution worldwide, accounting for about 10% of carbon emissions and 20% of wastewater, mainly from textile dyeing. One of the most widely used dyes is methylene blue, a thiazine-based cationic aromatic dye that threatens aquatic ecosystems and human health. Conventional wastewater treatments are less effective in Indonesia due to high operational costs. Photodegradation using semiconductor photocatalysts offers a simple and affordable alternative. Zinc oxide nanoparticles provide advantages over titanium dioxide, including lower cost and excellent electrical, mechanical, and optical properties. This study aims to synthesize zinc oxide nanoparticles using water hyacinth leaf extract as a natural reducing agent, combined with microwave irradiation to enhance eco-friendly synthesis. Methods: The extract was applied at concentrations of 4%, 8%, and 12%. Characterization using X-ray diffraction, Fourier-transform infrared spectroscopy, and scanning electron microscopy confirmed the formation of zinc oxide nanoparticles. Findings: The nanoparticles displayed average particle sizes of 134.42 nm, 120.54 nm, and 102.64 nm, respectively. Photodegradation performance analyzed by ultraviolet–visible spectrophotometry showed that methylene blue, with maximum absorbance at 664 nm, exhibited significant absorbance reduction after exposure to the nanoparticles, confirming their photocatalytic activity. Conclusion: Water hyacinth-assisted microwave synthesis produces zinc oxide nanoparticles efficiently, offering a low-cost and environmentally friendly solution with strong potential for textile dye wastewater treatment. Novelty/Originality of this article: The originality of this research lies in integrating water hyacinth extract and microwave irradiation, which accelerates nanoparticle synthesis while promoting sustainability, making it particularly suitable for application in developing countries.